An Assessment of the Investment Climate in Nigeria : The Challenges of Nigeria’s Private Sector - World Bank (World Bank, Washington, DC, 2016)
This report presents employment in Nigeria from a worker perspective as well as from a firm perspective. Using recent household data, the report complements the report ‘more, and more productive, jobs for Nigeria: a profile of work and workers’ (World Bank 2015) and provides an overview of employment opportunities in Nigeria from a labor force perspective. This report also intends to investigate the job agenda from a firm perspective and represents a first attempt to better understand the drivers of economic diversification, firm growth, and employment in Nigeria. The report draws on two different data sources: the General Household Survey (GHS) and the Enterprise Survey. The GHS provides data on the contribution of wage work to the Nigerian economy and its share of total employment. The GHS module on non-farm household enterprise provides information on the dynamics of micro and small enterprises, as well as the constraints they face. The Enterprise Survey, conducted in Nigeria from April 2014 to February 2015, was used to analyze the dynamics and constraints of the formal sector in Nigeria. The survey sample, which was limited to formally established companies with five or more employees, was composed of firms across nineteen states engaged in manufacturing, construction, or retail and wholesale trade. The results are presented in four regional groups: Lagos; Kano and Kaduna states; other southern states (Abia, Abuja, Anambra, Cross River, Enugu, Ogun, and Oyo); and other northern states (Gombe, Jigawa, Katsina, Kebbi, Kwara, Nasarawa, Niger, Sokoto, and Zamfara). A module on innovation was also administered to a portion of the survey sample. Details on the Enterprise Survey are provided in annex two.